IMPLEMENTATION OF RELIGIOUS MODERATION VALUES IN THE ISLAMIC RELIGIOUS EDUCATION CURRICULUM AT MADRASAH ALIYAH SAMUDERA PASAI MADANI ACEH BESAR - Miswar, Miswar; Quthni , Addar (Mereunoe: Education Journal, 2025)
Guidance for students in understanding religious moderation has been implemented in various ways at the Samudera Pasai Madani Islamic Senior High School in Aceh Besar. This is done through extracurricular activities at the school and also through internalization in Islamic Religious Education (IRE) subjects. The approach of this research is to use qualitative methods. This research is included in the field research category. The type of qualitative method used is descriptive qualitative with a case study approach. The primary data sources in this study are Islamic Religious Education Teachers, Students and Curriculum Representatives of Madrasah Aliayah. The results of the study show that 1). The method of Islamic Religious Education Teachers in implementing the values of religious moderation in the Islamic religious education curriculum at Madrasah Aliyah Samudera Pasai Madani Aceh Besar is through innovative teaching methods such as discussions, case studies, and project-based learning. This is effective in forming the character of students who are moderate, tolerant, and open to diversity, despite challenges related to the social backgrounds and religious understanding of students who are diverse. 2). The form of implication of Islamic Religious Education Teachers in implementing the values of religious moderation in the Islamic religious education curriculum at Madrasah Aliyah Samudera Pasai Madani Aceh Besar is through learning activities and character building. The integration of teaching materials, habituation of moderate attitudes, and extracurricular activities has succeeded in increasing students’ understanding of tolerance and harmony.